4th International Congress of Turkish Neuroendocrinology Society, Nov 26-28, 2020 (Virtual) Abstracts - Aslan, Gulnur; Sahna, Engin (Karger, 2021)
[Abstract Not Available]
4th International Congress of the Turkish-Neuroendocrinology-Society (TNED) -- NOV 26-28, 2020 -- ELECTR NETWORK
Keywords: Reperfusion arrhythmias; postconditioning; melatonin; nesfatin-1